Direct synthesis of LPG from syngas in a slurry phase. Issue 5 (21st October 2015) - Zhang, Qianwen; Ma, Ting; Zhao, Ming; Tomonobu, Teppei; Li, Xiaohong
Abstract : An original catalytic system for the synthesis of light hydrocarbons from syngas over a hybrid catalyst in the slurry phase was investigated. Abstract : An original catalytic system for the synthesis of light hydrocarbons from syngas over a hybrid catalyst in the slurry phase was investigated. N -cetane as the solvent remarkably increased the stability and activity of the catalyst by efficient removal of reaction heat. The synthesis of light hydrocarbons in a slurry phase requires the close contact of two components in a hybrid catalyst which is different from a gas phase reaction in a fixed bed. The replacement of Cu for Pd on the modification of β-zeolite increased the activity and stability of the catalyst and the selectivity of LPG by removing water from the zeolite. The effect of the Cu content on the performance of the process was systemically studied.